If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -4 + -9x = 41 Solving -4 + -9x = 41 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '4' to each side of the equation. -4 + 4 + -9x = 41 + 4 Combine like terms: -4 + 4 = 0 0 + -9x = 41 + 4 -9x = 41 + 4 Combine like terms: 41 + 4 = 45 -9x = 45 Divide each side by '-9'. x = -5 Simplifying x = -5
| B=900(1+0.1)6 | | 4(5m-3m)-9=3m-4 | | 4x-31/3=182/3 | | 5t-(3t+14)=2t-14 | | 5x^4-3x^2-1=0 | | 76=2x+16 | | x+2n=15n+23 | | 3a+13=9a | | 13-9x=133-37x | | x+2n=5n+23 | | 3x+(2/5)=4x+(4/5) | | (8x+12)=((5x-5)2) | | 6x-7=79-2x | | 9+4x=18x | | 9y-10=5y-54 | | 6x^4-12x^2= | | (3-4)+4*3*-3= | | 72x^2+56x/9x-7 | | 7(2x-8)-6=14x-62 | | 4(m-2)-7+2m=6(m+5) | | (8x+12)=(5x-5) | | 3z+7=35 | | 6(1/3)= | | 0*X=5 | | 8r+-5=51 | | 16+-9-2(4*3*1/2)= | | 8/3-2i | | -10+2m=8 | | 90+.4x=X | | 16+x^2=49 | | 5/4a+2=22 | | 8/(3-2i) |